Evaluation of non-radioactive in situ hybridisation method to detect Chlamydia trachomatis in cell culture. - Näher, H (1988)
A DNA probe combined with a non-radioactive stain was used to detect inclusions of Chlamydia trachomatis in cell culture. Of 39 positive cultures detected by monoclonal antibodies in combination with direct immunofluorescence, 35 were positive by the DNA hybridisation method, the sensitivity being 89.7%. Staining with iodine showed a sensitivity of 87.2%, corresponding to 34 positive cultures. The specificity of DNA hybridisation method was 100%, as all 162 cultures that were negative by the immunofluorescence method were also negative when assessed by the DNA hybridisation method.